High-grade microscopic hematuria in adult men can predict urothelial malignancy - Kotb, Ahmed Fouad; Attia, Doaa (Canadian Urological Association Journal, 2014)
Introduction: Microscopic hematuria in men younger than 40 is a confusing issue to urologists, especially when these men have normal radiological findings. We report our experience in looking for urologic malignancy in this group of patients. Methods: We conducted a prospective study for men with vague urological symptoms. We included men under 40 years old, men with microscopic hematuria greater than 25 red blood cells/high power field in 2 properly collected mid-stream urine samples, and men with free urine culture and normal multiphasic computed tomography abdomen and pelvis studies. All patients underwent diagnostic cystoscurethroscopy. If there were no lesions, multiple random biopsies were taken. In cases of apparently normal cystoscopic findings and associated renal colic, uretroscopy was done to the suspected side. Results: Only 20 patients fulfilled our inclusion criteria. The mean age of the patients were 34; 2 patients presented with pain. The other 18 patients were presenting with mild recurrent lower urinary tract symptoms. Cystoscopy showed small papillary low-grade tumour in 3 patients. All random biopsies were free of malignancy. Unilateral uretroscopy for the 2 cases presented with pain detected carcinoma in situ in one of them. Conclusion: Cystoscopy is highly recommended for young adult men, with significant levels of microscopic hematuria, due to the 20% incidence rate of associated urological malignancy. Random bladder biopsies, in the absence of suspicious lesions, have no diagnostic role, and should not be done. Uretroscopy is advised for patients with microscopic hematuria and loin pain, even in the absence of suspicious radiological findings.